Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kinerja Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening: Studi pada UIN Sunan Kudus - Dewi Sartika; Suhana Suhana (Fakultas Ekonomi & Bisnis, Univ, 2026)
This study aims to analyze the influence of emotional intelligence and spiritual intelligence on employee performance, with job satisfaction serving as an intervening variable, among the educational support staff at the State Islamic University (UIN) Sunan Kudus. The study employs a quantitative approach with an explanatory research design. The population consists of 55 educational support staff members, all of whom were included in the sample using a saturated sampling technique. Data were collected via a five-point Likert scale questionnaire and subsequently analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results indicate that emotional intelligence does not have a significant direct effect on employee performance but does have a positive and significant effect on job satisfaction. Conversely, spiritual intelligence is shown to have a positive and significant effect on both employee performance and job satisfaction. Furthermore, job satisfaction positively and significantly influences employee performance and mediates the effects of emotional and spiritual intelligence on performance. These findings suggest that enhancing emotional management capabilities and strengthening spiritual values ​​can boost job satisfaction, ultimately leading to improved performance among educational support staff. The study offers implications for human resource management in higher education, particularly regarding the design of policies that foster emotional intelligence, spiritual intelligence, and job satisfaction to enhance employee performance.